‘‘No idea…’’ : what do German economy and journalism elites know about digital disinformation characteristics? - Nils Vief and Marcus Bösch and Christian Stöcker (MISDOOM, 2023)
The spread of false information is a growing problem in societies governed by platforms that allow any person with internet access to create, share, and disseminate false information to a global audience. Besides more traditional strategies to distribute false information via images, text, and video, new ways have developed in recent times including multimodal memes, audio-visual deepfakes, and audio misinformation. We conducted guided interviews with 25 key actors from large corporations and media outlets in Germany in order to answer the research questions: How do people in charge identify online disinformation? What do they know about specific characteristics of disinformation including new ways of distributing fake information like audio misinformation or multimodal memes? Preliminary results indicate a lack of knowledge and awareness concerning characteristics of disinformation amongst these key players. We map out the need for optimized counter-measures, and suggest basic strategies to increase disinformation literacy.